Factorial analysis of growth parameters for mesophilic bacterium , Pseudomonas putida (ATCC 49128) - Ahmad, Mani Malam; Mohd Azoddein, Abd. Aziz; Jami, Mohammed Saedi (IIUM Press, 2018)
Studies on bacterial growth pattern from the conventional approach are defective due to their failure to explain the interactions or simply the complementary effects of the factors influencing the bacterial growth. In this study, the individual and collaborative effects of Pseudomonas putida growth variables were evaluated using a 2-level fractional factorial design of experiment (FFDOE). The growth of the organism was found to respond remarkably to different concentrations of nutrient media (carbon source) and the other independent variables. Factorial models were developed from the experimental design to study the individual and interactive effects of the studied parameters on the response. The studied parameters and their levels were as follows: nutrient concentration (4-16 g/L), acclimatization time (24-72 hrs), agitation (140-200 rpm), and temperature (30-40oC). These parameters were statistically validated using analysis of variance (ANOVA) and the results revealed that the model terms were statistically significant with an Fvalue of 415.17 at P <0.002. The growth factor with the most influence (positive) on the response was the nutrient concentration. The level of the parameters influence on the response was in the order of nutrient concentration > temperature > nutrient concentration versus temperature > agitation > nutrient concentration versus agitation. Based on the R2 and the adjusted R2 values of >95%, the estimated variables showed a high degree of relationship between the observed and the predicted values; thus, the predictive ability of the models was suggested. It could, therefore, be concluded that nutrient concentration, temperature, and agitation can greatly influence the growth of P. putida within a specific range.